Adaptive significance of within-site variation in morphological and reproductive traits of naturalized wild radish (Raphanus raphanistrum) populations in South-Western Australia - Bhatti, M.; Cocks, P.; Bennett, Sarita; Malik, A. (2016)
Genotypic variation between and within populations of the outbreeding wild radish (Raphanus raphanistrum L.), was studied using seeds collected from 55 sites across the West Australian wheat belt along 2 transects in December 1999 and February 2000. The seeds were grown at the University of Western Australia field station at Shenton Park, Perth, WA over the 2000 growing season, and 14 morphological and phenological characters were scored. A high degree of variation was present in all traits, and within site variation was greater than between sites. The greatest variation was recorded in the reproductive traits such as time to flowering, seed weight, and pod weight. Variation between sites was associated with geo-clusters based primarily on rainfall and temperature. Populations from sites with a high annual rainfall and low average temperature had longer and wider pods, larger seeds and pods with more segments, compared to populations from sites with a low annual rainfall and a high average temperature. These plants also tended to flower later than those from hotter, drier sites. The results show that wild radish in the wheat-belt of Western Australia has formed genotypically distinct populations in the 150 years since it was introduced, that are adapted to the climate at the site of collection.